Correction to: The Effect of Using Eugenol Essential Oil of Clove Leaf as a Feed Additive on The Carcass Percentage and Carcass Components of Broiler Chickens - Tahir, Muhammad; Hafsah, Hafsah; Widodo, Eko (Jurnal Agripet, 2025)
Corrections to: Jurnal Agripet, 24(2): 162-167. https://doi.org/10.17969/agripet.v24i2.28042Added Reference (cited in text but missing in references): Radiastuti, N., 2009. Pengujian antibakteri dari minyak atsiri bunga cengkeh, kulit kayu manis dan rimpang jahe terhadap B. subtillis, S. aureus, dan P. Aeruginosa. Berk. Penel. Edisi Khusus. 3C: 5155.Removed Reference (listed but not cited): Kardum, N., M. Glibetic., 2018. Polyphenols and their interactions with other dietary compounds. Adv. Food Nutr. Res. 84: 103144.These changes do not affect the articles results or conclusions.